Simulação de escoamentos bifásicos aplicando a técnica de fluidodinâmica computacional - Silva, Sávio Sayanne Andrade (2017)
Two-phase flows can be found in the most different fields of the chemical, food, energy conversion, materials processing, as well as in the oil and gas industry. In this last one, in particular, in sectors such as manufacturing and transport, these flows travel great distances in lines upward or downward, resulting in changes in the mixture properties. The correct understanding of this mixture behavior in each section of the flow has fundamental importance in order that problems related to the assurance of the flow could be foreseen and anticipated, also providing technical and economic viability of the oil field. Due to recent technological advances in areas such as modeling and simulation, application of alternative techniques such as computational fluid dynamics (CFD) has been of great value in these investigations, mainly due to its low cost when compared with the construction of experimental apparatus. In this context, the purpose of this work was to apply computational fluid dynamics to reproduction of the biphasic flow present in industrial pipes, based on the implementation of an interfacial algebraic model (AIAD). From the results reported on the wave behavior it was possible to qualitatively validate such model. Then, a parametric study was carried out to determine the behavior of the oil/gas interface over time, as well as the effects of oil viscosity and duct height. The results demonstrate that the transfer of the amount of movement has a great influence on the behavior of the liquid/gas interface, in addition, the increase of the viscosity of the liquid phase together with the equilibrium between the injection velocity of the phases are fundamental for a stratification of the flow of form faster.